An integrated reverse engineering and rapid prototyping approach towards reconstruction of damaged impeller. (2016) - Saurabh, Jain; Niranjan, Nigudkar N.; Hasan, Faisal; Kumar, Atul
With the advancement of technology it is now possible to have a reconstructed or reengineered product arising out of any damaged product or part by any digitisation techniques. The reengineered or reconstructed products may prove to be an economically viable option for manufacturing industries especially where higher costs are associated with products like turbine rotors, boiler components, auto components, etc. Also, in many cases, this technique bridges the gap between the actual products and their lost or damaged design data. In the present work, an integrated reverse engineering and rapid prototyping approach has been demonstrated for the reconstruction and subsequent finite element analysis of a damaged impeller. Further, the optimisation of the parameters is carried out for the reconstructed impeller. The results obtained for the reconstructed impeller are compared with that of the original rotor and the finding are discussed in light of some previous works conducted.